Instructional Barriers and Challenges Faced by Faculty and Students of Graduate School in One Hei in the New Normal Set Up - Jingco, Freya Gay; Brombuela, Glenn; Atienza, Demie; Caparas, Edith (Future Science / FSH-PH Publications, 2021)
The education system in our country also adjusted to the new normal set-up. The new normal set-up is not easy for everyone to immediately cope up with. It requires us to take things to a new approach of learning online. It pushed us to adapt to the settings we are not used to, and we are having difficulty coping with this set-up we are currently in. Also, the professors are having problems finding ways to provide a better way for the students to learn more effectively. From what we are having right now about the new way of education, there were several expected and known challenges that graduate students will meet and have met during their schooling. We cannot change the fact that our new way of living nowadays caused by a deadly virus leads us all into numerous difficulties to continue our everyday life. Specifically, this paper presented the experience by the respondents about the degree of online learning barriers. Identified barriers included in the study are administrative/instructor issues, social interactions, time and support for homework, technical skills, technical problems, academic skills, learner motivation, cost and access to the Internet. A survey questionnaire adapted from Muilenburg & Berge (2005) was used in this study.The weighted mean for measuring the challenges level is the statistical tool used in the data processing. Based on the results, Infrastructure and internet bandwidth should be the priority for investment. For higher education Institution, an increase awareness about online learning among teachers is encouraged. Teachers must attend and as much as possible, participate in webinars and open online courses (MOOCs) available. Moreover, it is highly recommended that before any online learning, qualified and trained online facilitators and technical support must be formed.